Analisis Bibliometrik: Media Pembelajaran Interaktif di Bidang Teknologi Pendidikan pada Database Scopus Tahun 2018-2024 - Fatihanursari Dikananda; Ahmad Rifai (Prosiding SISFOTEK, 2024)
This study aims to analyze the trends in the use of interactive learning media in the field of educational technology through a bibliometric approach. Interactive learning media encourage active engagement of learners and include mobile apps, interactive whiteboards and interactive videos. Studies show that interactive media improve students' motivation, learning outcomes and creative thinking skills. Bibliometric methods were used to explore and visualize research trends and collaborations between researchers and institutions in this field. Data was collected from academic databases that included scientific articles, conference proceedings and dissertations. Tools such as VOSviewer were used to map collaboration networks and keyword trends that revealed several key research themes, including the effectiveness of interactive learning media, the development of technology-based media, and their implementation in various educational contexts. This study provides an in-depth understanding of research developments in interactive learning media and identifies research gaps that could be a focus in the future. The results show a significant increase in the number of publications related to interactive learning media in recent years. The study also identifies key centers of research excellence and collaborations between institutions.